Remote sensing and GIS application for land resources appraisal of Ridhora watershed in Nagpur district, Maharashtra - KUCHANWAR, OMMALA D.; GABHANE, V. V.; INGLE, SAGAR N. (Journal of Soil and Water Conservation, 2021)
Accomplishment about morphological, physical and chemical characteristics of soil is an essential requirement for successful crop endowment and achievement in an area. Captivating this concept into jurisdiction, twelve representative soil series were exposed and mapped as series and complex with phases on 1:50000 scales based on landform-soil relationship in Ridhora watershed of Nagpur district of Maharashtra. Six major landform units viz. plateau top, escarpment, isolated mound, pediment, upper valley and lower valley, were identified and delineated. Based on image interpretation, seven major land use/ land cover were identified, i.e. cultivated land, wasteland with scrub, dense forest, moderately dense forest, degraded forest and habitation. Cultivated land is again classified into single and double crop based on temporal data. Soils on very gently sloping plateau top and moderately to steeply sloping escarpments and isolated hillocks are very shallow, somewhat excessively drained and classified as Typic Ustorthents. whereas soils on very gently sloping undulating land, foot slope, alluvial plain and valley are moderately deep to very deep, moderately well drained to well drained, very dark gray to very dark grayish brown in colour, calcareous and have clay textural class and qualify for Typic/Vertic Haplustepts. These soils were grouped into IIIes, IIIesf, IVs, IVsf, VIs, VIIe,VIIs and 2st, 3s, 3st, 4s, 4st and 5t land capability and irrigability subclasses, respectively. The land suitability evaluation indicates that Kachari sawanga-3 (99.69 ha), Bhiwari-2 (66.46), Ridhora-2 (358.04 ha) and Subkund-2 (238.70) series soils are highly suitable for cultivation of cotton, sorghum, soybean, pigeonpea, wheat, chickpea, groundnut and citrus whereas Kokarda-2 (180.00 ha), Mendhe pathar (120.00 ha), Kachari sawanga-2 (26.06 ha) and Bhiwari-1 (17.38 ha) series soils are not suitable for cultivation of cotton, sorghum, soybean, pigeon pea, wheat, chickpea, groundnut and citrus. Suitable conservation measures and interventions have been suggested to improve the productivity of these soils.